2002
DOI: 10.1063/1.1419210
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence from erbium-doped silicon nanocrystals in silica: Excitation mechanisms

Abstract: We develop a model for the excitation of erbium ions in erbium-doped silicon nanocrystals via coupling from confined excitons generated within the silicon nanoclusters. The model provides a phenomenological picture of the exchange mechanism and allows us to evaluate an effective absorption cross section for erbium of up to 7.3ϫ10 Ϫ17 cm 2 : four orders of magnitude higher than in stoichiometric silica. We address the origin of the 1.6 eV emission band associated with the silicon nanoclusters and determine abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 33 publications
3
101
1
Order By: Relevance
“…We recall that such an initial amplitude of Er PL attained very shortly after excitation ͑regime I͒ was also reported before. 23 Based on the total evaluation of optically active Er fraction, we conclude that the "residual concentration" of Er 3+ ions involved in the slow excitation/slow recombination process ͑regimes II and III͒ amounts to ϳ0.2% of the total Er content.…”
Section: B High-resolution Photoluminescence Kineticsmentioning
confidence: 99%
“…We recall that such an initial amplitude of Er PL attained very shortly after excitation ͑regime I͒ was also reported before. 23 Based on the total evaluation of optically active Er fraction, we conclude that the "residual concentration" of Er 3+ ions involved in the slow excitation/slow recombination process ͑regimes II and III͒ amounts to ϳ0.2% of the total Er content.…”
Section: B High-resolution Photoluminescence Kineticsmentioning
confidence: 99%
“…(1), we determine the effective cross section of the Si-nc mediated excitation as = 8.7± 0.3ϫ 10 −17 cm 2 , close to previous reports. 5,6 We note, that a similar value of can also be estimated from the general formula for excitation cross section of Er 3+ in crystalline Si. 13 The contribution from the Er 3+ ions directly excited in Sample No.…”
mentioning
confidence: 99%
“…For example, a number of studies have shown that the sensitized erbium luminescence in the SiO x system may be characterized by an effective excitation cross section ͑ ef f ͒ that takes into account absorption of pump photons by Si nanoclusters, followed by transfer of excitation to nearby erbium ions. [4][5][6][7][8][9] In this paper, we discuss the appropriateness of defining an effective cross section and suggest instead that a transfer coefficient is a more robust measure of sensitization.…”
Section: Introductionmentioning
confidence: 99%